RETRACTED: Perspectives for the development of safe-ecosystems based on 5-pl logistics in Russia - Chechenova L.M.; Toschev V.V. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001